HUMAN RESOURCE DEVELOPMENT AT PIEAS - A BRIEF HISTORICAL ACCOUNT - Hasan, B. A. (The Nucleus, 2020)
In this article the historical-role of the Pakistan Institute of Engineering and Applied Sciences (PIEAS) as the key Human Resource Development (HRD) centre of the Pakistan Atomic Energy Commission (PAEC) is described. This brief account covers a period of about 37 years, from 1967 to 2004 and goes on to describe the several transformations that a small and modest facility „Reactor School‟ went through by first growing into the famous „Centre for Nuclear Studies (CNS)‟ and later-on the present day PIEAS - as one of the most respected and prestigious degree awarding institute of the country. PIEAS was established to cater for the HRD needs of PAEC but now its scope has been broadened to a much wider extent to address the national needs. Presently PIEAS is imparting education to the postgraduate level in 7 different areas with a diversity that ranges from Nuclear Engineering to Nuclear Medicine, while several other graduate and postgraduate degrees are in the pipeline. The pioneering role of its founders and the award-winning contributions of PIEAS graduates are also presented.